Myristoylation of the RING Finger Z Protein Is Essential for Arenavirus Budding - Perez, Mar (American Society for Microbiology, 2004)
The arenavirus small RING finger Z protein is the main driving force of arenavirus budding. The primary structure of Z is devoid of hydrophobic transmembrane domains, but both lymphocytic choriomeningitis virus (LCMV) and Lassa fever virus Z proteins accumulate near the inner surface of the plasma membrane and are strongly membrane associated. All known arenavirus Z proteins contain a glycine (G) at position 2, which is a potential acceptor site for a myristoyl moiety. Metabolic labeling showed incorporation of [(3)H]myristic acid by wild-type Z protein but not by the G2A mutant. The mutation G2A eliminated Z-mediated budding. Likewise, treatment with the myristoylation inhibitor 2-hydroxymyristic acid inhibited Z-mediated budding, eliminated formation of virus-like particles, and caused a dramatic reduction in virus production in LCMV-infected cells. Budding activity was restored in G2A mutant Z proteins by the addition of the myristoylation domain of the tyrosine protein kinase Src to their N termini. These findings indicate N-terminal myristoylation of Z plays a key role in arenavirus budding.